Should women with incontinence and prolapse do abdominal curls? - Simpson, S.; Deeble, M.; Thompson, Judith; Andrews, A.; Briffa, K. (Springer U K, 2016)
© 2016 The International Urogynecological Association Introduction and hypothesis: Urinary incontinence (UI) and pelvic organ prolapse (POP) occur in 30–50 % of women. It is proposed that increases in intra-abdominal pressure (IAP) caused by high-intensity activities may contribute to symptoms of pelvic floor dysfunction. There is a lack of consensus as to the type of activity restrictions that may be necessary in this population. The objective was to determine the change in IAP (cm H20) during abdominal curl and cough in patients with UI and POP attending urodynamic evaluation. Methods: In this exploratory descriptive study, 30 women with diagnosed POP and/or UI were recruited. IAP was measured by multichannel cystometry whilst participants performed three abdominal curls and three maximal coughs. Results: Participants were aged 29–80 (mean 56.2) years, and mean ± standard deviation (SD) body mass index (BMI) was 29.9 (5.2) kg/m-2. All participants had UI and 12 had POP in addition to UI. IAP increased significantly from rest to abdominal curl and cough (19.6–50.3 and 78.4, respectively; p < 0.001). Greater pressures were generated in the women with POP than in those with UI only (p = 0.02). There were large variations in change in pressure between participants (1.67–159.66 for cough; 4–81.67 for abdominal curl). Conclusion: The large variability in IAP generated during abdominal curl and cough suggests some current recommendations may be unnecessarily restrictive in some women but important in others. Advice for women with pelvic floor dysfunction undertaking tasks that increase IAP needs to be individualized.